Aplikasi Media Pembelajaran Aksara Jawa untuk Siswa Sekolah Dasar menggunakan Augmented Reality berbasis Android - Echa Jessica Putri; Sutarman Sutarman; Saucha Diwandari (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Javanese script is one of the local learning materials for Javanese that has been taught since elementary school. The characters are difficult for students because they are rarely used in everyday activities. The growing development of learning media technology can be utilized to attract students' attention and make learning activities easier. One example is the use of augmented reality technology. The purpose of this study is to develop a learning medium that can make it easier for students to learn Javanese characters. Methods used in research to develop these applications are waterfall models, which include need analysis, data collection, system design, implementation, and testing. Literature studies and interviews are used for data collection. In this study, it can be seen that the application has been successfully created and developed. Based on system testing using black-box testing, the features of the application ran according to plan and obtained 91.85% of the feasibility test results using the Likert-scale test criteria, which meant that the application was worthy of use.